ANALISA UMUR ALAT POTONG MESIN MILLING DENGAN MATERIAL SUS 420 - Qomarotun Nurlaila (Universitas Riau Kepulauan, 2020)
This research was performed on 3 cutting tools which are tool drill 1.8mm, 2.5mm in diameter and tool back chamfer 2.2mm in diameter. Hardness value from each cutting tool was approximately 300 HRC. Meanwhile, material used in this research is SUS 420 that has hardness value 262HRC. To perform cutting on work unit, it was requested higher hardness value for cutting tool compared to work unit (SUS420). Tool drill 1.8mm in diameter was used at first pitting process (rapping), tool drill 2.5mm in diameter was used at second pitting process (finishing) and tool back chamfer 2.2mm in diameter was used at the last pitting process. This research was performed to define the tool life of cutting tools that utilized in milling machine from work unit material SUS 420. From this research, it was expected maximum amount that can be achieved from cutting tools every replacement can be obtained. At the end of study, when the replacement time of cutting tools can be defined, the loss of not good product (because of cutting) can be avoided. Based on the result, tool life of cutting tool was 920 cuttings.